The international right of rights? Article 25(a) of the ICCPR as a human right to take part in international law-making - Maisley, Nahuel (2017)
Most international legal scholars consider that although the inclusion of civil society in international law-making would be desirable, it is not yet legally required. In this article, I argue that civil society groups already do have a right to participate in international lawmaking. Although I believe there are various paths that can be taken to defend this idea, in this article I focus on only one. I hold that the right can be derived from Article 25(a) of the International Covenant on Civil and Political Rights, which grants every citizen 'the right and the opportunity ... to take part in the conduct of public affairs, directly or through freely chosen representatives'. Specifically, I interpret Article 25(a) in accordance with the Vienna Convention on the Law of Treaties. I argue, first, that the article can be interpreted as applying internationally (considering the ordinary meaning, the context, the subsequent practice and other rules of international law) and, second, that it should be interpreted in this way (if read in good faith and considering the object and purpose of the treaty).